Quality control of ultrasound for fetal biometry: results from the INTERGROWTH‐21st Project. (26th July 2018) - Cavallaro, A.; Ash, S. T.; Napolitano, R.; Wanyonyi, S.; Ohuma, E. O.; Molloholli, M.; Sande, J.; Sarris, I.; Ioannou, C.; Norris, T.; Donadono, V.; Carvalho, M.; et al.
ABSTRACT: Objective: To assess a comprehensive package of ultrasound quality control in the Fetal Growth Longitudinal Study of the INTERGROWTH‐21 st Project, a large multicenter study of fetal growth. Methods: Quality control (QC) measures were performed for 20 313 ultrasound scan images obtained prospectively from 4321 fetuses at 14–41 weeks' gestation in eight geographical locations. At the time of each ultrasound examination, three fetal biometric variables (head circumference (HC), abdominal circumference (AC) and femur length (FL)) were measured in triplicate on separately generated images. All measurements were taken in a blinded fashion. QC had two elements: (1) qualitative QC: visual assessment by sonographers at each study site of their images based on specific criteria, with 10% of images being re‐assessed at the Oxford‐based Ultrasound Quality Unit (compared using an adjusted kappa statistic); and (2) quantitative QC: assessment of measurement data by comparing the first, second and third measurements (intraobserver variability), remeasurement of caliper replacement in 10% (interobserver variability), both by Bland–Altman plots and plotting frequency histograms of the SD of triplicate measurements and assessing how many were above or below 2 SD of the expected distribution. The system allowed the sonographers' performances to be monitored regularly. Results: A high level of agreement between self‐ and external scoring was demonstrated for all measurements (κ = 0.99 (95% CI, 0.98–0.99) for HC, 0.98 (95% CI, 0.97–0.99) for AC and 0.96 (95% CI, 0.95–0.98) for FL). Intraobserver 95% limits of agreement (LoA) of ultrasound measures for HC, AC and FL were ± 3.3%, ± 5.6% and ± 6.2%, respectively; the corresponding values for interobserver LoA were ± 4.4%, ± 6.0% and ± 5.6%. The SD distribution of triplicate measurements for all biometric variables showed excessive variability for three of 31 sonographers, allowing prompt identification and retraining. Conclusions: Qualitative and quantitative QC monitoring was feasible and highly reproducible in a large multicenter research study, which facilitated the production of high‐quality ultrasound images. We recommend that the QC system we developed is implemented in future research studies and clinical practice. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.